Benefit of triple-frequency on cycle-slip detection - Zhao, Dongsheng; Hancock, Craig M.; Roberts, Gethin Wyn; Lau, Lawrence (2018)
At the time of writing, all the Global Navigation Satellite Systems (GNSS) support or are designed to support triple- or multi- frequency, which is expected to have advantages over single- and dual- frequency. This paper will conduct research on how triple-frequency can benefit the cycle-slip detection process. Correctly detecting and repairing cycle slips can help extend the latency of the fixed ambiguities, estimate the ionospheric delay, reduce the measurement noise and finally improve the positioning precision of the carrier phase. This paper will firstly review the widely used cycle-slip detection methods, including high-order phase differencing, Doppler integration and the ionospheric residual. For applying triple-frequency in cycle-slip detection, we will modify the Hatch-Melbourne-Wübbena combination to eliminate the effect of the ionospheric bias and reduce the measurement noise on the detection value. The triple-frequency method can detect and correct cycle slips instantaneously. All the mentioned methods will be tested using triple-frequency Galileo data observed in static condition. The results show that the performance of the triple-frequency method has a higher success rate and a lower missed detection compared to those using single-frequency, especially in detecting small cycle slips in observation with large intervals. Although the ionospehric residual provides higher success rates at low elevation angles, the triple-frequency method is more advanced than the ionospheric residual, which cannot decide the magnitude of the cycle slips easily.